Implementation of Green Banking Practices among State-Owned Banks in Indonesia: Toward Sustainable and Ethical Financial Transformation - Anggita Mulia Pangesti; Fauzatul Laily Nisa (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2024)
This study examines the implementation of green banking practices among Indonesia’s state-owned banks (Bank BUMN) and their contribution to sustainable and ethical financial transformation. As part of the global shift toward environmentally responsible finance, green banking has emerged as a critical framework for integrating ecological considerations into banking operations, investment decisions, and corporate governance. Using a qualitative descriptive approach supported by secondary data and document analysis, this research explores how state-owned banks apply sustainable finance principles in alignment with national regulations, including OJK Regulation No. 51/POJK.03/2017 on Sustainable Finance and Law No. 32/2009 on Environmental Protection and Management. The findings reveal that the implementation of green banking within Indonesia’s BUMN banks has reached a maturity level of nearly 100 percent compliance with sustainable finance indicators, as reflected in policy integration, sustainable lending programs, and environmentally friendly internal operations. These practices have reduced carbon dependency, enhanced energy efficiency, and positioned banks as key enablers of Indonesia’s low-carbon economic transition. However, challenges remain in the form of limited human resource capacity, inconsistent managerial commitment, and complex regulatory harmonization. The study concludes that the long-term success of green banking requires continuous institutional support, technological innovation, and cross-sectoral collaboration. It contributes to the broader discourse on sustainable finance by highlighting the strategic role of public banks in balancing economic growth, environmental stewardship, and ethical responsibility within emerging economies.